INORGANIC OXIDE SYNTHESIS FROM ACEH BOVINE BONE USING THE PRECIPITATION METHOD FOR BIOMASS TRANSESTERIFICATION - Amlia, Nisa; Ramli, Muliadi; Rossani, Ratu Balqis; Mitaphonna, Rara; Lubis, Surya; Idris, Nasrullah; Saiful, Saiful; Fathurrahmi (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
Inorganic oxide nanoparticles synthesized from Aceh bovine bone were successfully prepared using the precipitation method, with pH variations of 8 and 10 adjusted using NH₄OH as the precipitating agent and pH regulator. The resulting nanocatalysts were characterized using XRD, FTIR, and SEM-EDX, and their catalytic activity was evaluated through the transesterification of RBDPO. XRD and FTIR analyses confirmed the presence of hydroxyapatite (Ca₁₀(PO₄)₆(OH)₂), calcium oxide (CaO), and calcium carbonate (CaCO₃) as the main components in catalysts synthesized at pH 8 and pH 10. SEM micrographs revealed spherical particle morphologies, while EDX analysis showed calcium as the dominant element, with contents of 55.44% and 57.19%, respectively. The average crystallite sizes, calculated using the Debye–Scherrer equation, were 31.63 nm (CB-P8C) and 31.31 nm (CB-P10C). Catalytic activity tests demonstrated that the catalyst synthesized at pH 10 exhibited higher performance, achieving a biodiesel yield of 98.11%, compared to 92.66% for the catalyst synthesized at pH 8. Quality assessment of both biodiesel samples confirmed that their acid values, density, and viscosity met the Indonesian National Standard (SNI 04-7182-2015). This approach highlights a sustainable pathway for converting biowaste into efficient catalysts for green fuel production.